2016
DOI: 10.20546/ijcmas.2016.502.065
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Glucose Isomerase from Bacillus thuringiensis under Different Treatments

Abstract: Various microorganisms have been found to produce glucose isomerase (Deshmukh et al., 1994;Belfaquih and Penninckx., 2000;Givry and Duchiron, 2007). The conversion of glucose to fructose chemically has been known to demand high pH and temperature. The possibility of producing fructose chemically from glucose has been studied by Barker et al. (1973).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The activation of α-glucosidase by Ca 2+ could be due to the in forcing of the interactions inside α-glucosidase molecules and by the binding of Ca 2+ to the autolysis site. Ca 2+ activated other enzymes such as phytase [17] and glucose isomerase [18].…”
Section: Effect Of Different Cations On α-Glucosidase Activity From Pmentioning
confidence: 99%
“…The activation of α-glucosidase by Ca 2+ could be due to the in forcing of the interactions inside α-glucosidase molecules and by the binding of Ca 2+ to the autolysis site. Ca 2+ activated other enzymes such as phytase [17] and glucose isomerase [18].…”
Section: Effect Of Different Cations On α-Glucosidase Activity From Pmentioning
confidence: 99%
“…Glucose isomerase produced from Actinoplanes missouriensis exhibited Km value of 1.33 moles for glucose [15]. The Km reported by El-Shora et al [24] from Bacillus thuringiensis was 8 mM for glucose. Dhungel et al [4] reported 0.45 M as Km and 0.18 U/mg as Vmax for glucose by using psychrotolerant Streptomyces sp.…”
Section: Achromobacter Xylosoxidans Mck-4 Started Accumulating Intracellular Enzyme After 12 Hrsmentioning
confidence: 99%
“…GI from Thermoanaerobacter ethanolicus was found to isomerize best at 85°C by Fan et al [27] and the enzyme produced by Thermotogane apolitana was extremely thermostable with an optimum temperature at 95°C [31]. El-Shora et al [24] found out that glucose isomerase from Bacillus thuringiensis isomerizing best at 50°C. Lee et al [32] observed the optimal activity of GI from Dunaliellater tiolecta to be 60°C.…”
Section: Achromobacter Xylosoxidans Mck-4 Started Accumulating Intracellular Enzyme After 12 Hrsmentioning
confidence: 99%
See 2 more Smart Citations